2023
DOI: 10.22541/essoar.167840001.13313960/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preferential Hydrologic States and Tipping Characteristics of Global Surface Soil Moisture

Abstract: This a preprint and has not been peer reviewed. Data may be preliminary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Global estimates of surface soil texture are accessed from Poggio et al (2021). Global estimates of θ RS preferential hydrologic states, tipping characteristics and other variables discussed in this study are freely available in NetCDF format on HydroShare through Sehgal and Mohanty (2023).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Global estimates of surface soil texture are accessed from Poggio et al (2021). Global estimates of θ RS preferential hydrologic states, tipping characteristics and other variables discussed in this study are freely available in NetCDF format on HydroShare through Sehgal and Mohanty (2023).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The number of frequency peaks was designed to represent the strength of soil moisture seasonality. A unimodal distribution represents weak seasonality under persistently wet or dry climates, whereas a bimodal distribution represents strong seasonality (Sehgal & Mohanty, 2023; Figure 2a,b). However, applications to a wider range of climates showed that bimodal distributions had multiple causes.…”
Section: Case Studies: Challenges Applying Signatures In Large Sample...mentioning
confidence: 99%
“…These can be inferred from spatial maps of fraction of time a pixel spends in dry or wet regime at any given season. The advantage of such a division is that it naturally advances the widely accepted ideas of preferential states of soil moisture (D'Odorico & Porporato, 2004;Grayson et al, 1997;Sehgal & Mohanty, 2023) and Budyko framework (Budyko, 1974), while forgoing earlier terminology conflicts. Additionally, the division allows for quantification of SM-ET coupling using 𝑑 𝑊 which has extensions to understand corresponding entropy production (described in section 3.4) in SM to ET anomaly transference.…”
Section: A Comprehensive Sm-et Coupling Frameworkmentioning
confidence: 99%
“…Another conjecture from the coupling-aridity tradeoff and entropy production capacity is that for a given amount of flux and land temperature, temperate climates bear the least efficiency compared to other hydroclimates for unit anomaly transference. This could be argued to be most likely due to their bistable nature for soil moisture subsidence (Sehgal & Mohanty, 2023).…”
Section: Lower Bound Of Entropy Production and Its Seasonal Variationsmentioning
confidence: 99%